1990
DOI: 10.1177/026835559000500304
|View full text |Cite
|
Sign up to set email alerts
|

Three Tests of Microcirculatory Function in the Evaluation of Treatment for Chronic Venous Insufficiency

Abstract: No investigation exists which has been shown to detect accurately microcirculatory improvement following treatment for chronic venous insufficiency. This study examines three possible techniques for doing so. Fourteen patients with chronic venous insufficiency and fourteen controls underwent measurement of transcutaneous PO2, 133xenon clearance from the skin and subcutaneous tissues and laser–Doppler flowmetry in the gaiter region. Patients with venous disease then followed a regime of intermittent pneumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Using simultaneous fluorescence and light capillary microscopy, Franzeck et al 16 have described the appearances of capillary loops that are filled with red blood cells, but do not appear to be perfused. They suggest that this may be due to capillary “thrombosis.” After investigation by xenon clearance and oxygen return times, 17,18 we have not been able to support earlier hypotheses suggesting that venous ulceration is due to tissue hypoxia 6,19 …”
Section: The “White Cell Trapping” Hypothesiscontrasting
confidence: 61%
“…Using simultaneous fluorescence and light capillary microscopy, Franzeck et al 16 have described the appearances of capillary loops that are filled with red blood cells, but do not appear to be perfused. They suggest that this may be due to capillary “thrombosis.” After investigation by xenon clearance and oxygen return times, 17,18 we have not been able to support earlier hypotheses suggesting that venous ulceration is due to tissue hypoxia 6,19 …”
Section: The “White Cell Trapping” Hypothesiscontrasting
confidence: 61%
“…Homans in 1930 demonstrated the direct relationship between venous hypertension in the legs and increased capillary intraluminal pressures[ 38 ] It follows that arteriovenous fistulas in the skin of the lower extremities cause hypoxia, resulting in changes to the skin and tissues structures, but tissue hypoxia hypothesis was challenged by compensation in capillary growth and shunting mechanisms. Furthermore, studies of skin oxygenation suggest that hypoxia is not a major cause of skin changes[ 12 14 41 ] Thus, hypoxia results seem to be odd, however, the study of Burnand et al . [ 9 ] seems to favor the fibrin cuff hypothesis, which describes the primary problem as venous hypertension in the lower extremities causing leakage of plasma proteins, particularly fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Moreover, the topical application of xenon-133 in skin suffering from venous disease yielded a similar clearance as in controls. 25 Finally, in clinical studies, ulcers were shown to heal despite the existence of fibrin cuffs. 26 Today, there is no doubt about the existence of fibrin cuffs: they are regarded as signs of endothelial damage or dysfunction.…”
Section: Fibrin Cuff Theorymentioning
confidence: 99%
“…Similar to investigations performed with native capillary microscopy as described above, a decline in flow after leg dependency due to the vasoconstrictor response induces a reduction in the laser Doppler flux. 25 Even in young healthy individuals, laser Doppler flux is lower in the gaiter region than over the shin or the dorsum of the foot. This low laser Doppler flux may be an early sign of a predilection area for ulcer formation in oncoming decades.…”
Section: Fluorescence Microlymphographymentioning
confidence: 99%